2015
DOI: 10.15253/2175-6783.2015000300004
|View full text |Cite
|
Sign up to set email alerts
|

Activities of living of disabled people according to the Roper-Logan- Tierney model of nursing

Abstract: Objective: to identify the activities of living of disabled people by applying the Roper-Logan-Tierney Model of Nursing.Methods: cross-sectional study conducted in private university. The population comprised 13 people with physical andsensory disabilities, who practiced water sports. Data collection occurred through structured script. Results: mostparticipants came from the capital, were male, aged between 19 and 69 years. The most affected activities of living wereMaintaining a safe environment, Mobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…In another study of 13 people with physical or sensory disabilities practicing water sports in a sports park, researchers found that maintaining safe environment and mobilization were the most affected life activities (17) . In the current study, participants in the role of blind person also had impaired mobility and the feeling of being in unsafe environment.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 13 people with physical or sensory disabilities practicing water sports in a sports park, researchers found that maintaining safe environment and mobilization were the most affected life activities (17) . In the current study, participants in the role of blind person also had impaired mobility and the feeling of being in unsafe environment.…”
Section: Discussionmentioning
confidence: 99%
“…Ressaltase que a utilização deliberada e sistemática de todas as etapas do PE na assistência às pessoas em neurorreabilitação tem conferido ao enfermeiro maior visibilidade e reconhecimento profissional, e enriquecido seu conhecimento na neurorreabilitação, com a construção de um vocabulário específico para denominar os diagnósticos e intervenções de enfermagem que são próprios da sua prática (4,6,7) .…”
Section: Têm Investido Nos úLtimosunclassified
“…Entender como ela ocorre e quais os estímulos que podem estar causando a dor dos pacientes em neurorreabilitação ajudam o enfermeiro a avaliar de forma mais eficaz a adaptação da pessoa (1) . Portanto, avaliar a dor constitui uma premissa na prática do enfermeiro, buscando um cuidado individualizado, a fim de aliviar a dor (4) . (4) .…”
Section: Introductionunclassified
See 1 more Smart Citation